Reviewing Islamic Criminal Punishment Views On Corruption Asset Confirmation Without Crimination - Mustaufiq, Mustaufiq; Kurniati, Kurniati; Misbahuddin, Misbahuddin (Al-'Adl, 2023)
The paper discusses the Islamic criminal system's views on confiscating corruptors’ assets, which has been proposed for a draft law since 2012. The confiscation of assets is a solution to provide a deterrent effect and restore state losses. This study uses library research methods with a normative approach to answering the question, "what is the view of Islamic crime on the concept of confiscation of assets without punishment?". The results state that the confiscation of assets resulting from criminal corruption is a form of ta'zir punishment that has been accommodated in Islamic criminal law, Islamic criminal law allows doubling corporal punishment and fines, to provide a deterrent effect on criminal offenders. Confiscation of assets has also fulfilled the essence of Islamic punishment in fulfilling the rights of Allah, rewarding in kind for the actions committed, and remorse that creates a desire to repent for the perpetrators.